Subjective Stroke Impact and Depressive Symptoms: Indications for a Moderating Role of Health-Related Locus of Control - Zirk, Miriam; Storm, Vera (Frontiers in Psychiatry, 2019)
Background: Stroke is one of the most common causes of death and disability worldwide. Subsequently, depression occurs in about one third of the stroke survivors. Health-related locus of control might serve as a modifiable cognitive factor to aid the recovery process. Aims: The present study aims to explore the role of health-related locus of control in the relation between subjective stroke impact and depressive symptoms after stroke. Methods: In the present cross-sectional study, N = 44 stroke patients (n = 18 female and n = 24 male) were recruited at two rehabilitation centers in Germany. Mean age was M = 65.8 (SD = 11.52, Range = 48-88). Self-report instruments included the stroke impact scale, health-related locus of control questionnaire, and Beck depression inventory. Data analysis was conducted in R using correlation and regression methods. Results: Subjective stroke impact and depressive symptoms were not directly associated (rs = -.20, p = .216). However, health-related locus of control moderated the relationship between subjective stroke impact and depressive symptoms (β = -0.42, p = .015), revealing a stronger negative relationship when control of one`s health was attributed externally. Conclusion: The results indicate that health-related locus of control plays a role in the relationship of subjective stroke impact and depressive symptoms. It is recommended to focus on control beliefs during the recovery process of stroke survivors. For developing targeted interventions, it is necessary to further investigate these associations while incorporating various health-related control belief concepts and replicate the present findings among larger samples.